2011
DOI: 10.1590/s0034-737x2011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Aceitabilidade de feijão preto (Phaseolus vulgaris L.), fortificado com micropartículas de ferro

Abstract: Acceptability of black beans (Phaseolus vulgaris L.) fortified with iron microparticlesThis study aimed to evaluate the acceptability of black beans (Phaseolus vulgaris L.) fortified with iron micro particles, to be further used in the prevention and control of iron-deficiency anemia. Three samples of stewed black bean were prepared: 1) no addition of microencapsulated ferrous sulfate (control); 2) 5 mg of iron were added to each serving spoon of beans; and 3)10 mg of iron added to each serving spoon of beans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Previous research has shown that encapsulating ferrous sulfate in pea protein spray-dried particles is a promising method, considering the iron bioaccessibility 16 and the potential to mask the metallic taste. 16,17 Moreover, the incorporation of such ferrous sulfate pea protein spray-dried particles (here referred to as iron-loaded pea protein particles) in cooked black beans 17 and in a banana candy 16 showed good consumer acceptability. It should be noted, though, that the iron-loaded pea protein particles were incorporated after the food was processed, which means that the iron-loaded pea protein particles were not exposed to further food process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that encapsulating ferrous sulfate in pea protein spray-dried particles is a promising method, considering the iron bioaccessibility 16 and the potential to mask the metallic taste. 16,17 Moreover, the incorporation of such ferrous sulfate pea protein spray-dried particles (here referred to as iron-loaded pea protein particles) in cooked black beans 17 and in a banana candy 16 showed good consumer acceptability. It should be noted, though, that the iron-loaded pea protein particles were incorporated after the food was processed, which means that the iron-loaded pea protein particles were not exposed to further food process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the "mass fortification or universal", which consists of adding micronutrients to foods consumed by the vast majority of the population, being regulated by governments; the "fortification in open market", which comprehends the fortification of food by industry on its own initiative and "Directed fortification", which is the fortification of foods eaten by groups at high risk of nutritional deficiency (Ferreira et al, 2015).…”
Section: Fortificationmentioning
confidence: 99%
“…O feijão comum (Phaseolus vulgaris, L.) é um alimento básico do cardápio de grande parte da população brasileira, de fácil aquisição e baixo custo, tendo grande importância nutricional, econômica, social e cultural. Os grãos desta leguminosa representam 11,2% das calorias diárias ingeridas na dieta tradicional, fornecendo nutrientes essenciais como proteínas, carboidratos complexos, ácidos graxos insaturados, ferro, cálcio, magnésio, zinco, vitaminas (principalmente do complexo B), fibra alimentar e elevado teor de lisina [4][5][6][7] .…”
Section: Introductionunclassified